Nível de atividade física, estado nutricional e níveis de BACE 1 e BACE 2 em idosos neurologicamente saudáveis e com doença de Alzheimer - Fuzaro Junior, Gilson [UNESP] (2015)
Alzheimer's disease (AD) is a neurodegenerative, progressive and causes cognitive impairment in the elderly. Besides drug therapy, nonpharmacological alternatives such as physical activity and nutritional counseling, can help in treating the disease. The influence of these factors in some biomarkers such as β-secretase, has been related to changes in certain tables of the disease. The objective of this study was to analyze the level of physical activity, nutritional status and platelet levels of BACE BACE 1 and 2 in elderly patients with Alzheimer's disease in mild and moderate stages and cognitively preserved elderly. Also compare groups and to correlate these variables. To do so, participated in the study 32 elderly with AD and 32 healthy elderly. To check the level of physical activity the elderly used an accelerometer and the questionnaire Baecke modified for the elderly. The assessment of nutritional status consisted of the collection of anthropometric measurements: weight (kg), height (m), circumference and skinfold thickness. It has also been applied to Mini Nutritional Assessment. Through blood collection, platelet levels of BACE and BACE 1 of 2 groups were analyzed. Furthermore, screening tests were applied cognitive function, depressive symptoms and the staging of the attendees. For data analysis, the normality of the sample using the Shapiro-Wilk test was verified. For parametric data, we used the Student t test and Pearson's correlation to non-parametric data, the Mann-Whitney U test and Spearman correlation. It was admitted a significance level of p <0.05. The results indicate a significant difference in the average level of physical activity at concentrations of BACE 1 and 2 and the variable Mini Nutritional Assessment between the groups, with the DA group had lower levels of physical activity, higher concentrations of BACE and worse nutritional status. In addition, the Spearman test showed negative correlation between the...